Functional study of laminin subunit α5 in high-grade serous ovarian cancer - Wang Tianli; Shaojing Li; Rong Zhang (Journal of Ovarian Research)
Abstract Objective To investigate the expression of LAMA 5 (laminin subunit α5) in high-grade serous ovarian cancer and its relationship with the prognosis of ovarian cancer patients. Methods: The expression of LAMA5 in high-grade serous ovarian cancer was explored through the ovarian cancer sample information in multiple databases and real-time fluorescent quantitative PCR (Real Time Quantitative PCR, RT-qPCR). Effect of LAMA5 on the proliferation and migration of ovarian cancer cells. The possible mechanism of LAMA 5 affecting the malignant process of ovarian cancer was searched by GSEA analysis. Results: Based on bioinformatics analysis and RT-qPCR verification in multiple databases, it was found that LAMA5 was highly expressed in serous ovarian cancer, which was related to clinical stage and indicated poor prognosis. High expression of LAMA 5 can promote the proliferation and migration of ovarian cancer cells. Based on the GSEA analysis, it is suggested that the process of LAMA5 promoting the occurrence and development of ovarian cancer may be related to the mitotic pathway of the spindle (Mitotic Spindle) and the Hedgehog (Hh) signaling pathway. Conclusion: LAMA 5 may be used as a clinical marker for evaluating the prognosis of serous ovarian cancer and a new therapeutic target.